Tomato seed bio-priming with Pseudomonas aeruginosa strain PAR: a study on plant growth parameters under sodium fluoride stress - Singh, Anamika; Patani, Anil; Patel, Margi; Vyas, Suhas; Verma, Rakesh Kumar; Amari, Abdelfattah; Osman, Haitham; Rathod, Lokendra; Elboughdiri, Noureddine; Yadav, Virendra Kumar; Sahoo, Dipak Kumar; Chundawat, Rajendra Singh; et al. (Frontiers in Microbiology, 2024)
The primary goal of this experiment is to examine the effectiveness of Pseudomonas aeruginosa Strain PAR as a rhizobacterium that promotes plant growth in mitigating the negative effects of fluoride-induced stress in tomato (Lycopersicon esculentum Mill.) plants. Sixteen rhizobacterial strains were tested for plant growth-promoting (PGP) attributes, with isolates S1, S2, and S3 exhibiting different characteristics. Furthermore, growth kinetics studies revealed that these isolates were resilient to fluoride stress (10, 20, 40, and 80 ppm), with isolate S2 exhibiting notable resilience compared to the other two strains. Phylogenetic analysis revealed isolate S2 as Pseudomonas aeruginosa Strain PAR. Physiological analyses demonstrated that the Pseudomonas aeruginosa Strain PAR had a beneficial impact on plant properties under fluoride stress, comprising seed germination, root length, shoot height, relative water content and leaf area, the strain also impacted the buildup of glycine betaine, soluble sugar, and proline, demonstrating its significance in enhancing plant stress tolerance. In P. aeruginosa Strain PAR-treated plants, chlorophyll content increased while Malondialdehyde (MDA) levels decreased, indicating enhanced photosynthetic efficiency and less oxidative stress. The strain modified antioxidant enzyme action (catalase, ascorbate, glutathione reductase, peroxidase, and superoxide dismutase), that contributed to improved stress resilience. Mineral analysis revealed a decrease in sodium and fluoride concentrations while increasing magnesium, potassium, phosphorus, and iron levels, emphasizing the strain's significance in nutrient management. Correlation and principal component analysis revealed extensive correlations between physiological and biochemical parameters, underscoring Pseudomonas aeruginosa Strain PAR's multifaceted impact on plant growth and stress response. This study offers valuable information on effectively utilizing PGPR, particularly P. aeruginosa Strain PAR, in fluoride-contaminated soils for sustainable agriculture. It presents a promising biological strategy to enhance crop resilience and productivity.